2022
DOI: 10.1155/2022/8650099
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Sinus Involvement and Near Miss Mediastinitis following Mandibular Tooth Infection Treated during the COVID-19 Pandemic: Clinical Diagnosis and Treatment

Abstract: Odontogenic infections represent a frequent condition that in some cases, if not treated promptly, can spread quickly to the rest of the body and turn into life-threatening infections. In this work, the case is reported of a 59-year-old woman, diabetic and overweight, who presented to the Odontostomatology and Otolaryngology Section of the Policlinic of Bari with mandibular tooth infection that had developed into a deep neck space infection leading to the involvement of cavernous sinuses and near mediastinum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…In the literature, several studies described the possible evolution of sialadenitis in DNI, especially for elderly and immunocompromised people [13]. In 10% of the cases that we collected, DNIs were related to infections of unknown origin, and this data is supported by recent literature reports showing that in up to 25% of cases of DNIs, it is not possible to identify the primary source of infection [14].…”
Section: Discussionsupporting
confidence: 77%
“…In the literature, several studies described the possible evolution of sialadenitis in DNI, especially for elderly and immunocompromised people [13]. In 10% of the cases that we collected, DNIs were related to infections of unknown origin, and this data is supported by recent literature reports showing that in up to 25% of cases of DNIs, it is not possible to identify the primary source of infection [14].…”
Section: Discussionsupporting
confidence: 77%
“…9 Other studies have reported a variety of ODS complications associated with the COVID-19 pandemic, which included a series of cases of ODS with invasive fungal mucormycosis and a case of ODS with cavernous sinus involvement and systemic spread with mediastinitis. 10,11 In our cohort, one patient from the COVID group presented with an intracranial abscess requiring an oro-maxillofacial intervention, endoscopic sinus surgery, orbitofrontal craniotomy, and extended antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…They postulated that the infection spreads through direct routes, such as submucosal or thrombophlebitis, or indirect routes, such as hematogenous spread through the maxillary alveolar marrow or through the facial veins passing through the pterygoid plexus to the orbit, face, brain, or systemically 9 . Other studies have reported a variety of ODS complications associated with the COVID‐19 pandemic, which included a series of cases of ODS with invasive fungal mucormycosis and a case of ODS with cavernous sinus involvement and systemic spread with mediastinitis 10,11 . In our cohort, one patient from the COVID group presented with an intracranial abscess requiring an oro‐maxillofacial intervention, endoscopic sinus surgery, orbitofrontal craniotomy, and extended antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The types of surgical techniques that are currently available are conventional scalpel surgery and laser surgery. The conventional cold-blade method has all the side effects of classical surgery, such as tissue bleeding with the need for suturing and possible bacterial overinfection of the surgical site [12,13].…”
Section: Introductionmentioning
confidence: 99%